STRATEGIES FOR TEACHING WRITING IN EFL CLASS AT A SENIOR HIGH SCHOOL IN INDONESIA1 - Jurianto Jurianto; Salimah Salimah; Deny A Kwary (Soegijapranata Catholic University, 2015)
Writing skill has been considered the most difficult language skill to master, and teaching the skills has also been not simple. Part of a research report on teaching writing in English at a senior high school in Surabaya, this paper is aimed to demonstrate that English teachers at the school are skillful and resourceful in teaching writing. With reference to 11 elements or strategies of writing instruction discussed in Graham and Perin (2007), five English teachers at die school were interviewed. The interview guide includes 24 questions centered on the 11 elements. Interview results show that the teachers make vise of most elements or strategies in their English classes. The teachers explained that such strategies as collaborative writing, sentence combining, prewriting, inquiry activities, and study of models are conducted frequently in the classroom. They found the strategies important and helpful for teaching writing skills in English to their students. The findings indicate that a variety of writing instruction strategies have been part of their teaching practice and that they are experienced in teaching writing skills in English to adolescent students.